Quel rôle pour la langue de référence dans les représentations des apprenants ? Le cas de l'évaluation en langue étrangère - Rachel Varshney (Recherches en didactique des langues et des cultures)
This research project explores learner's representations of strategic L1 use in the foreign language classroom and highlights both the positive or negative roles attributed to the L1 in the language learning process – particularly with respect to language assessment – continuing to explore the relatively understudied domain of student representations within a scholarly context. Surveying a population of Australian (N=18) and French students (N=25), this study uses both questionnaire and interview responses in order to analyse the roles allocated to the L1 with respect to learning outcomes. The results indicate that students have a very balanced view of the L1 with respect to the learning of grammar, vocabulary and social aspects, yet its use in assessment aspects appears much more advantageous. The importance of this study and its findings is in recognizing the complex nature of learner representations in order to facilitate a discussion that is based more on the reality of language teaching, with the hope of renewing classroom practices.